TOURISM IMPACTS ON THE AYUTTHAYA WORLD HERITAGE SITE: MEASURING THE PERCEPTIONS OF THE HOST COMMUNITY - Ongkhluap, Somyot (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2014)
ABSTRACT This research aims to determine the Ayutthaya local communities’ values with regards to heritage and tourism and to measure the perceptions of the local communities toward the impacts of tourism on the Ayutthaya World Heritage Site and on the local community of Ayutthaya within which they live.The methodology proposed in this study was a community-based process that begins with the values of the local communities and relates these to all the tourist activities in Ayutthaya to generate a matrix that measures the perception of impacts on the local community. The results revealed that overall perceptions of the impacts of tourism received quite a positive response and were regarded as having a positive relationship with community values. The impacts of tourism on economic values were perceived as highly positive, followed by socio-cultural and environmental values which were in varying degrees less so. On the other hand, the impacts of tourism on environmental values was perceived as being highly negative followed by socio-cultural and economic which were seen as less negative. Keywords: Ayutthaya, community, heritage, tourism impacts, perception บทคัดย่อ งานวิจัยนี้มุ่งค้นหาคุณค่าของชุมชนท้องถิ่นในอยุธยา และวัดการรับรู้ของชุมชนท้องถิ่นในอยุธยาที่มีต่อผลกระทบของการท่องเที่ยวต่อเมืองมรดกโลกอยุธยาและต่อการคุณภาพชีวิตของชุมชนท้องถิ่นเอง ระเบียบวิธีวิจัยที่ใช้ในการศึกษาครั้งนี้เป็นกระบวนการศึกษาที่ใช้ชุมชนเป็นฐาน ซึ่งเริ่มด้วยการค้นหาคุณค่าของชุมชนท้องถิ่น และสร้างเครื่องมือวิจัยที่เป็นตารางความสัมพันธ์ระหว่างคุณค่าดังกล่าวกับกิจกรรมการท่องเที่ยวในอยุธยาซึ่งจะนำไปใช้ในการวัดการรับรู้ของชุมชนท้องถิ่นของอยุธยานั้นเอง ผลการศึกษาพบว่า ชุมชนท้องถิ่นส่วนใหญ่รับรู้ว่าการท่องเที่ยวส่งผลกระทบด้านบวกมากกว่าด้านลบ โดยรับรู้ว่ามีผลกระทบด้านบวกต่อเศรษฐกิจมากที่สุด ตามมาด้วยสังคมวัฒนธรรม และสิ่งแวดล้อมตามลำดับ ในทางตรงกันข้าม ชุมชนท้องถิ่นเห็นว่าการท่องเที่ยวส่งผลกระทบด้านลบต่อสิ่งแวดล้อมมากที่สุด ตามมาด้วยด้านสังคมวัฒนธรรม และด้านเศรษฐกิจ ตามลำดับ คำสำคัญ: อยุธยา, ชุมชน, มรดก, ผลกระทบของการท่องเที่ยว, การรับรู้